Storage of WDGS under hermetic and non-hermetic conditions: Effect on sensory properties, microorganisms, mycotoxins and nutritional value. (January 2019) - Alvarez, Estefania; Cardoso, Marcelo; Depetris, Gustavo; Castellari, Claudia; Cristos, Diego; Montiel, María Delfina; Bartosik, Ricardo
Abstract: WDGS production in Argentina substantially increased in the last 5 years and become a frequent constituent for feed diets. However, due to the extremely high moisture content of the product, quality deterioration occurs in a few days under aerobic conditions; which creates a series of logistical problems for expanding the use of WDGS far away from production plants. Silo bag technology, a flexible hermetic storage system extensively used in Argentina, could be a good alternative for extending the storage time of WDGS. Thus, the main goal of this research was to compare the effect of hermetic and non-hermetic storage of WDGS using several quality parameters. Samples of WDGS from three different ethanol production plants were stored in hermetic (small scale silo bags) and non-hermetic conditions at 16 °C (60 days hermetic and 20 days no-hermetic). WDGS quality evolution was evaluated through sensory, microbiological, biochemical, nutritional and toxicological parameters. Results indicated that in the non-hermetic treatment, even though no evidence of nutritional quality losses was found in the mass of WDGS, spoilage developed at the surface after 10 day of storage. Additionally, evidence of mycotoxin formation was found (DON) during aerobic storage, implying that mycotoxin tests should be routinely implemented. On the contrary, hermetic storage in silo bag allowed a proper ensiling process, extending the shelf life of the product and preventing mycotoxins development for at least 60 days. Highlights: Storage of WDGS under hermetic and non-hermetic condition was evaluated. Hermetic storage favored the ensiling process. Hermetic condition further reduced pH and favored conservation during 60 days. After 10 days of aerobic storage, intense spoilage developed on surface of product. Mycotoxin develop under aerobic storage condition, but not in hermetic storage.